Beyond performance legitimacy: Procedural legitimacy and discontent in China - Mayling Birney (London School of Economics and Political Science (LSE), Department of International Development, 2017)
Conventional wisdom maintains that the Chinese Communist Party is upheld by performance-based legitimacy. Yet what about procedural legitimacy? Analyzing national survey data on China, this study finds that governance procedures affect the legitimacy of subnational levels of governing, if not necessarily that of the national level. Good governance contributes to trust in local leaders, while corruption not only detracts from trust in local and regional leaders, it increases the public's willingness to protest. This reality was not well-incorporated into the core legitimacy-building approach adopted during the Hu-Wen era. Despite low priority and constrained governance reforms, the main legitimation strategy in the Hu-Wen era remained focused on performance-as growth and equity-even as the public valued procedural legitimacy. While performance legitimacy and traditional legitimacy are also shown to be important phenomena, this study highlights why these are fragile bases for legitimacy, especially considering rising modernization forces and economic slowdown.
Keywords: 330; legitimacy; trust; governance; corruption; protest; election; modernization; China